179k views
4 votes
How can I solve this equation if x = -2 and y = -3? 3y (x + x² - y) I've also included a picture of the equation.

How can I solve this equation if x = -2 and y = -3? 3y (x + x² - y) I've also included-example-1

1 Answer

1 vote

In order to calculate the value of the equation, let's first use the values of x = -2 and y = -3 in the equation and then calculate every operation:


\begin{gathered} 3y(x+x^2-y) \\ =3\cdot(-3)\cdot(-2+(-2)^2-(-3)) \\ =-9(-2+4+3) \\ =-9\cdot5 \\ =-45 \end{gathered}

Therefore the final result is -45.

User Nikhil Padmanabhan
by
5.0k points